2021
DOI: 10.17576/jsm-2021-5002-10
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and LC-MS Data Comparison from Lichen Parmotrema praesorediosum in Malaysia

Abstract: The research study regarding antimicrobial activity of pure compounds and LCMS data comparison from extract of lichen Parmotrema praesorediosum in Bangi, Selangor, Malaysia. Antimicrobial activity of acetone, ethanol, and methanol extracts as well as five compounds, namely methyl divaricatinate, methyl haematommate, methyl chlorohaematommate, methyl β-orsellinate, and vinapraesorediosic acid from methanol extract were identified for the microbial activity against four b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The status of bacteria with multidrug resistance against beta-lactams (Am, Ax , Am/sulbactam, and CX) as determined by AST was further confirmed by the detection of resistance genes (bla TEM , bla SHVm , bla OXA , and bla CTX−M ) using PCR, in accordance with a previous study [28], using the resistance gene primers listed in Table-2.…”
Section: Detection Of Resistance Genes In Mdr E Coli and Salmonella Spp Isolated From Diseased Animals By Pcrsupporting
confidence: 82%
“…The status of bacteria with multidrug resistance against beta-lactams (Am, Ax , Am/sulbactam, and CX) as determined by AST was further confirmed by the detection of resistance genes (bla TEM , bla SHVm , bla OXA , and bla CTX−M ) using PCR, in accordance with a previous study [28], using the resistance gene primers listed in Table-2.…”
Section: Detection Of Resistance Genes In Mdr E Coli and Salmonella Spp Isolated From Diseased Animals By Pcrsupporting
confidence: 82%
“…This finding was in line with another study that found that extracts of acetone, methanol, petroleum ether, and diethyl ether from three species of foliose lichen, Dirinaria picta, Dirinaria papillulifera, and Dirinaria applanata, had antimicrobial activity against human pathogenic bacteria and fungi using a well-diffusion method against human pathogenic bacteria and fungi [78,79]. Earlier reports also indicated that extracts of P. praesorediosum in methanol, acetone, hexane, and dichloromethane have inhibitory action against bacterial and fungal diseases [80].…”
Section: Discussionsupporting
confidence: 86%